1991
DOI: 10.1136/gut.32.7.787
|View full text |Cite
|
Sign up to set email alerts
|

Prospective hospital based study on persistent diarrhoea.

Abstract: A total of 383 children aged less than 5 years suffering from acute watery diarrhoea or dysentery were studied in hospital to determine the rate of persistent diarrhoea. Altogether 335 (87.5%) recovered within 13 days. Only in 48 (12.5%) did the diarrhoea continue for 14 days or more, and they were considered as having persistent diarrhoea. Children aged between 7 and 18 months had a significantly increased incidence of persistent diarrhoea. Children suffering from grade II-IV malnutrition constituted the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
3
7
0
Order By: Relevance
“…Shigella flexneri, Shigella boydii, Salmonella typhimurium, Enteroagrregative E. coli, Enteropathogenic E. coli, Aeromonus sp. and rotavirus, was observed which corroborates the findings of other studies in developing countries (25)(26)(27). The most likely explanation for the high isolation rate of enteropathogens in our study population is that the initial infection persisted even at the time of enrolment, reflecting dehydration and high purging rates of these cases.…”
Section: Discussionsupporting
confidence: 92%
“…Shigella flexneri, Shigella boydii, Salmonella typhimurium, Enteroagrregative E. coli, Enteropathogenic E. coli, Aeromonus sp. and rotavirus, was observed which corroborates the findings of other studies in developing countries (25)(26)(27). The most likely explanation for the high isolation rate of enteropathogens in our study population is that the initial infection persisted even at the time of enrolment, reflecting dehydration and high purging rates of these cases.…”
Section: Discussionsupporting
confidence: 92%
“…Our study like many others confirm that pathogenic E. coli and Shigella dominate in developing countries, 68,72,77,108 compared with Salmonella, Shigella, and Campylobacter in industrialized countries. 109111 These pathogens are transmitted through mainly fecal oral route, 112–115 and contaminated food or water.…”
Section: Discussionsupporting
confidence: 89%
“…Bacteria were the main pathogens identified by a majority of studies, and the high rates of diarrhoeagenic E. coli spp ., Shigella, Salmonella spp ., and Campylobacter spp ., is consistent with the prevailing risk factors, 9 , 11 , 106 , 107 and likely reflects the availability of bacteriological diagnostic techniques. Our study like many others confirm that pathogenic E. coli and Shigella dominate in developing countries, 68 , 72 , 77 , 108 compared with Salmonella, Shigella, and Campylobacter in industrialized countries. 109 111 These pathogens are transmitted through mainly fecal oral route, 112 – 115 and contaminated food or water.…”
Section: Discussionsupporting
confidence: 88%
“…In Dutta et al study, Grade II-IV was observed in 70.8% of all cases of persistent diarrhoea. 5 In present study, it was 65.71%. Under nutrition was common in male children (87.18%) when compared to female children (83.87%).…”
Section: Discussionmentioning
confidence: 66%
“…1 Dutta et al in their study also concluded that children aged between 7 and 18 months had increased incidence of persistent diarrhoea. 5 Persistent diarrhoea was observed in 55.71% male children and 44.29% female children, with slight male preponderance. This was similar to the study done by Mbori-Ngacha et al 6 Under nutrition was observed in 85.71% of all cases of persistent diarrhea.…”
Section: Discussionmentioning
confidence: 99%